Tissue engineering applications of recombinant human collagen: a review of recent progress - Cao, Lili; Zhang, Zhongfeng; Yuan, Dan; Yu, Meiping; Min, Jie (Frontiers in Bioengineering and Biotechnology, 2024)
With the rapid development of synthetic biology, recombinant human collagen has emerged as a cutting-edge biological material globally. Its innovative applications in the fields of material science and medicine have opened new horizons in biomedical research. Recombinant human collagen stands out as a highly promising biomaterial, playing a pivotal role in crucial areas such as wound healing, stroma regeneration, and orthopedics. However, realizing its full potential by efficiently delivering it for optimal therapeutic outcomes remains a formidable challenge. This review provides a comprehensive overview of the applications of recombinant human collagen in biomedical systems, focusing on resolving this crucial issue. Additionally, it encompasses the exploration of 3D printing technologies incorporating recombinant collagen to address some urgent clinical challenges in regenerative repair in the future. The primary aim of this review also is to spotlight the advancements in the realm of biomaterials utilizing recombinant collagen, with the intention of fostering additional innovation and making significant contributions to the enhancement of regenerative biomaterials, therapeutic methodologies, and overall patient outcomes.